Lack of peroxisomal catalase affects heat shock response in Caenorhabditis elegans - Musa, Marina (2023)
Exact mechanisms of heat shock-induced lifespan extension, although documented across species, are still not well understood. Here, we show that fully functional peroxisomes, specifically peroxisomal catalase, are needed for the activation of canonical heat shock response and heat-induced hormesis in Caenorhabditis elegans Although during heat shock, the HSP-70 chaperone is strongly up-regulated in the WT and in the absence of peroxisomal catalase (ctl-2(ua90)II), the small heat shock proteins display modestly increased expression in the mutant. Nuclear foci formation of HSF-1 is reduced in the ctl-2(ua90)II mutant. In addition, heat-induced lifespan extension, observed in the WT, is absent in the ctl-2(ua90)II strain. Activation of the antioxidant response and pentose phosphate pathway are the most prominent changes observed during heat shock in the WT worm but not in the ctl-2(ua90)II mutant. Involvement of peroxisomes in the cell-wide cellular response to transient heat shock reported here gives new insight into the role of organelle communication in the organism's stress response.